2021
DOI: 10.1007/s10461-021-03159-2
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Barriers to HIV PrEP Uptake and Adherence Among Black and Hispanic/Latinx Transgender Women in Southern California

Abstract: Black and Hispanic/Latinx transgender women in the United States (U.S.) are disproportionately affected by HIV. Preexposure prophylaxis (PrEP) reduces risk of HIV infection but PrEP uptake remains low among Black and Hispanic/Latinx transgender women. Between July 2018 and August 2019, we conducted individual interviews with 30 Black and Hispanic/ Latinx transgender women who were prescribed PrEP through a PrEP demonstration project and 10 healthcare providers who provide PrEP services to transgender women in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(102 citation statements)
references
References 37 publications
3
76
0
23
Order By: Relevance
“…Three qualitative studies were identified that found depression to be a barrier to PrEP access. A study conducted in southern CA with 30 TGW found that mental health concerns were identified as barriers to PrEP care [ 48 ]. Similarly, another study conducted in southern CA with 37 individuals, the majority of whom were transgender, identified that mental disorder symptoms made PrEP access difficult [ 49 ].…”
Section: Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three qualitative studies were identified that found depression to be a barrier to PrEP access. A study conducted in southern CA with 30 TGW found that mental health concerns were identified as barriers to PrEP care [ 48 ]. Similarly, another study conducted in southern CA with 37 individuals, the majority of whom were transgender, identified that mental disorder symptoms made PrEP access difficult [ 49 ].…”
Section: Depressionmentioning
confidence: 99%
“…PrEP adherence was a lower priority compared to mental health symptoms. Of note, some participants indicated that taking their PrEP on schedule was a way for them to positively cope with mental health symptoms [ 48 ].…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 HIV preexposure prophylaxis (PrEP) presents an opportunity to address this disparity; however, there is a considerable lack of research on PrEP with this population. [4][5][6][7][8] Existing research has predominantly focused on documenting facilitators and barriers to PrEP uptake among TGW/TFI, including PrEP awareness, attitudes, acceptability, and eligibility. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Few studies in the United States have included a substantial sample of TGW/TFI on PrEP, 8,10 and none have closely examined dynamics over time of real-world PrEP use (ie, in the absence of research incentive or intervention).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Negative opinions of PrEP fueled by misinformation, such as side effects occurring that are not associated with PrEP, presented an additional barrier. 10 PrEP was also associated with promotion of risk, HIV-related stigma, and promiscuity. 11 Previous experiences of discrimination in health care is the most notable barrier to PrEP for trans communities.…”
Section: Introductionmentioning
confidence: 97%